Antimicrobial potential of medicinal plant extract towards multi drug resistant microbial strain / Norazlina Ahmad, Choo Chee Yan and Zaidatul Azmi Abd Rahman - Ahmad, Norazlina; Choo, Chee Yan; Abd Rahman, Zaidatul Azmi (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2006)
Aim: Some traditional Malay medicinal plants were selected and evaluated for the antimicrobial activity potential against sensitive strains of Staphylococcus aureus and Eschericia coli and multidrug resistant strains of methicillin resistant Staphylococcus aureus (MRSA) and extended spectrum beta lactamase E.coli (RESCO). Method: The ground dried leaves or seeds were extracted with 70 % aqueous methanolic solution for two days. The solution was subsequently filtered and dried in vacuo using a rotary evaoparator. The dried methanolic extract was later dissolved in 2 % DMSO and subjected to antimicrobial evaluation by means of micro well plate dilution method. Conclusion: All the traditional Malay medicinal plants inhibited the growth of Staphylococcus aureus strains with inhibition index between 0.36 and 0.84. The leaves of Cassia alata and seeds of Cassia surattensis exhibited moderate activity against both the MRSA and ESBL E.coli strains. All the Lycopodium species evaluated inhibited the growth of Staphylococcus aureus strain with inhibition index ranging from 0.61 to 1.10. Three of the Lycopodium species inhibited the growth of the MRSA strain.